Expression patterns of hair-related keratins and epithelial keratins in onychopapilloma: The significance of clarifying the origin of onychopapilloma - Liu, Mengxi; Li, Fang; Wang, Xiaoqing; Liu, Zhenru; Wong, Hoi Shiwn; Zhou, Yuan; Wang, Daguang (Frontiers in Medicine, 2022)
Background Onychopapilloma is generally recognized as a benign tumor of the nail bed and distal matrix. However, the origin of onychopapilloma has not been explained yet. Objective To clarify the origin of onychopapilloma, we detected the expression patterns of hair-related keratins and epithelial keratins, which are expressed specifically in the nail unit. Materials and methods The clinical and histopathologic features of 11 patients with onychopapilloma were analyzed, and the expression patterns of hair-related and epithelial keratins were detected. Results Histologically, all subjects showed acanthosis, papillomatosis and matrix metaplasia within the nail bed. Immunohistochemically, the expression pattern of keratins in our standard nail unit was consistent with previous reports. “Nail matrix-related keratins” HK31, HK34, HK85, and HK86 were only expressed in the nail matrix, and “Nail bed-related keratins” HK75 and K6/K16 were only expressed in the nail bed. However, in onychopapilloma, whether adjacent to the matrix or in the distal nail bed, all cases were positive for nail bed-related keratins and HK31 but negative for other nail matrix-related keratins. Conclusion Our study suggests that onychopapilloma may originate from the nail bed rather than the nail matrix. Furthermore, the expression of nail bed-related keratins and HK31 could be used as diagnostic markers of onychopapilloma.